Concessions, traditions, and staying safe: Considering sport, food, and the lasting impact of the Covid-19 pandemic - Seaman, A. N. (The Sport Journal, 2021)
Food is integral to the culture, infrastructure, and economics of sport. Sport`s unique food traditions engage spectators and athletes alike and facilitate the cultivation of social connections as well as contribute to the game day atmosphere. However, the topic has received little attention from scholars. Regardless, the Covid-19 pandemic has and will continue to disrupt the relationship between sport and food well into the future. This paper provides a review of the scant research available on food and sport and considers how each aspect of sport`s culinary landscape will be affected by Covid-19.